STUDENTS’ MOTIVATION IN ENGLISH SPEAKING LEARNING USING E-MODULE IN FOURTH SEMESTER OF ENGLISH EDUCATION STUDENTS AT MUHAMMADIYAH KOTABUMI UNIVERSITY - Rulik Setiani; Nurul Aulia; Elis Susanti; Dewi Sri Kuning (Relawan Jurnal Indonesia, 2022)
Students who learn English are said to be successful if they can use the language to communicate. Therefore, students are expected to be able to communicate using English fluently. However, in reality students rarely use English even in speaking class. The aim of this study was to describe students’ motivation in English speaking learning using E-Module in fourth semester of English education students at Muhammadiyah Kotabumi University. This research was quantitative descriptive method. This research conducted at Muhammadiyah Kotabumi University. The sample were 44 students who were determined by using total sampling technique. The research instrument used in the research for collecting the data was a questionnaire. There were 50 statements in the questionnaire, then the score categorized into three categories such as low, medium, and high. The results of the analysis showed that there were 9 students or 20% categorized as low, 30 students or 68% students were categorized as medium, and 5 students or 12% students were categorized as high. It can be concluded that students’ motivation in English speaking learning using E-Module in fourth semester of English education students at Muhammadiyah Kotabumi University was medium.